Pengaruh Indeks Bursa Regional Terhadap Indeks Harga Saham Gabungan (IHSG) - Margarita Ekadjaja (Jurnal Ekonomi, 2015)
In relation to fast economic growth in Indonesia and followed by the growth of the stock exchange, investing in the stock exchange is become one of the profitable choices for the investor. The main indicator of Indonesian stock exchange performance is called IHSG. This research aims to describe the correlation between regional index (STI Index and KLCI)and IHSG either simultaneously or partially in BEI. The sample used in this research is the regional index during 2008-2012. The model of analysis used in this research is multiple regression analysis. Simultant was used to test the influence from the entire/all variable regional index to IHSG with a significant level of 5%. The research stated that simultaneously there was a significant correlation between regional Index (STI and KLCI) to IHSG the Fhitung > Ftabel (326.4711 > 3.35). Partially there was a significant correlation between STI and KLCI to IHSG and there was a significant correlation among regional Index (STI and KLCI)to the IHSG the significance in 5%.